Optimal training strategy for body weight support treadmill training to enhance lower limb motor function and activity of daily living in persons with stroke: a systematic review and meta-analysis of randomized controlled trials - Shi, Yan; Liu, Junying; Zhang, Xinxin (Frontiers in Neurology, 2025)
ObjectiveThis meta-analysis aimed to investigate the effect of body weight support treadmill training (BWSTT) on lower limb motor function and daily living activities in a person with a stroke while also exploring the optimal training strategy.MethodsSix databases (PubMed, Web of Science, The Cochrane Library, CNKI, Wanfang, and SinoMed) were searched up to August 2025. Randomized controlled trials involving persons with stroke, BWSTT, and outcomes measured by the Fugl-Meyer assessment of lower extremity and Barthel Index scores were included. The risk of bias was assessed using the RoB-2 tool of the Cochrane Collaboration, and the certainty of evidence was assessed using the GRADE tool.Results25 studies with 1,749 people with stroke were incorporated into the meta-analysis. The meta-analysis demonstrated that BWSTT significantly outperformed the control group in improving both the Fugl-Meyer lower extremity score (MD = 4.80, 95% CI: 2.90–6.71, p < 0.001) and Barthel Index score (MD = 10.53, 95% CI: 7.61–13.46, p < 0.001). The certainty of evidence was rated as “very low.” The most effective interventions were observed in persons with a disease duration of 3–6 months (Fugl-Meyer: MD = 4.72, 95% CI: 1.54–7.89, p = 0.004; Barthel: MD = 17.58, 95% CI: 11.75–23.40, p < 0.001), intervention time of 4–8 weeks (Fugl-Meyer: MD = 5.78, 95% CI: 3.80–7.76, p < 0.001; Barthel: MD = 12.85, 95% CI: 3.84–21.87, p = 0.005), body weight support over 30% (Fugl-Meyer: MD = 4.51, 95% CI: 1.75–7.28, p = 0.001; Barthel: MD = 10.79, 95% CI: 6.91–14.67, p < 0.001), and gait speeds of 0.2 m/s or higher (Fugl-Meyer: MD = 4.01, 95% CI: 1.62–6.40, p = 0.001; Barthel: MD = 10.61, 95% CI: 1.13–20.10, p = 0.03).ConclusionBWSTT improved the lower limb function and daily activities of persons with stroke, with optimal outcomes at disease duration of 3–6 months or undergoing interventions for 4–8 weeks, and more than 30% of the maximum body weight support level or using a gait speed exceeding 0.2 m/s. It is unclear whether persons with disease durations of 3–6 months could achieve the same outcomes as those undergoing 4–8 weeks of intervention. The very low quality of evidence suggests that the conclusions require further validation through high-quality randomized controlled trials.Systematic review registrationhttp://www.crd.york.ac.uk/PROSPERO/, identifier: CRD42023486562.